Ghana : Joint Staff Assessment of the Poverty Reduction Strategy Paper Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2004)
The Joint Staff Assessment (JSA) of the Poverty Reduction Strategy Paper Annual Progress Report on Ghana evaluates the strengths and weaknesses of poverty reduction objectives and strategies. The 2003 Annual Progress Report (APR) of the authorities' poverty reduction strategy provides a review of recent developments and outcomes under the first year of implementation. Structural reform in certain sectors, such as power and education, contributes toward the achievement of the goal of eliminating gender disparity in access to primary education.